Characterization of Natural, Decellularized and Reseeded Porcine Tooth Bud Matrices - Traphagen, Samantha B. (2012)
Dental tissue engineering efforts have yet to identify scaffolds that instruct the formation of bioengineered teeth of predetermined size and shape. Here we investigated whether extracellular matrix (ECM) molecules present in natural tooth scaffolds can provide insight on how to achieve this goal. We describe methods to effectively decellularize and demineralize porcine molar tooth buds, while preserving natural ECM protein gradients. Natural tooth ECM composition was assessed using histological and immunohistochemical (IHC) analyses of fibrillar and basement membrane proteins. Our results showed that Collagen I, Fibronectin, Collagen IV, and Laminin gradients were detected in natural tooth tissues, and retained in decellularized samples. Second harmonic generation (SHG) image analysis and 3D reconstructions were used to show that natural tooth tissue exhibited higher collagen fiber density, and less oriented and less organized collagen fibers, as compared to decellularized tooth tissue. We also found that reseeded decellularized tooth scaffolds exhibited distinctive collagen content and organization as compared to decelluarized scaffolds. Our results show that SHG allows for quantitative assessment of ECM features that are not easily characterized using traditional histological analyses. In summary, our results demonstrate the potential for natural decellularized molar tooth ECM to instruct dental cell matrix synthesis, and lay the foundation for future use of biomimetic scaffolds for dental tissue engineering applications.